The Tongue Enables Computer and Wheelchair Control for People with Spinal Cord Injury - Kim, Jeonghee (Sci Transl Med, 2013)
The Tongue Drive System (TDS) is a wireless and wearable assistive technology, designed to allow individuals with severe motor impairments such as tetraplegia to access their environment using voluntary tongue motion. Previous TDS trials used a magnetic tracer temporarily attached to the top surface of the tongue with tissue adhesive. We investigated TDS efficacy for controlling a computer and driving a powered wheelchair in two groups of able-bodied subjects and a group of volunteers with spinal cord injury (SCI) at C6 or above. All participants received a magnetic tongue barbell and used the TDS for five to six consecutive sessions. The performance of the group was compared for TDS versus keypad and TDS versus a sip-and-puff device (SnP) using accepted measures of speed and accuracy. All performance measures improved over the course of the trial. The gap between keypad and TDS performance narrowed for able-bodied subjects. Despite participants with SCI already having familiarity with the SnP, their performance measures were up to three times better with the TDS than with the SnP and continued to improve. TDS flexibility and the inherent characteristics of the human tongue enabled individuals with high-level motor impairments to access computers and drive wheelchairs at speeds that were faster than traditional assistive technologies but with comparable accuracy.